The Influence of Leadership Style on Employee Performance through Employee Job Satisfaction - Maharani, Sonyta Dinda (Nur Science Institute, 2023)
The purpose of this study is to analyze: 1) the influence of leadership style on job satisfaction of Novotel Solo Hotel employees, 2) the influence of leadership style on the performance of Novotel Solo Hotel employees, and 3) the effect of job satisfaction on the performance of Novotel Solo Hotel employees. This research is a quantitative research. The sample in this study was 75 employees of Novotel Solo Hotel. Data collection was carried out using questionnaires and documentation. The data was analyzed using path analysis with the help of SPSS software. The results of this study show 1) leadership style has a positive and significant effect on job satisfaction of Novotel Solo Hotel employees. This can be seen from the regression coefficient of leadership style 1.687, and tcount of 19.853 and the significance level of 0.000. 2) Leadership style has a positive and significant effect on the performance of Novotel Solo Hotel employees. This can be seen from the leadership style regression coefficient of 0.892, and tcount of 1:8.492 as well as a significance level of 0.000. 3) Job satisfaction has a positive and significant effect on the performance of Novotel Solo Hotel employees. This can be seen from the job satisfaction regression coefficient of 0.487, and tcount of 18.799 as well as a significance level of 0.000.